2021
DOI: 10.12659/msm.935496
|View full text |Cite
|
Sign up to set email alerts
|

Remote Home-Based Exercise Program to Improve the Mental State, Balance, and Physical Function and Prevent Falls in Adults Aged 65 Years and Older During the COVID-19 Pandemic in Seoul, Korea

Abstract: Background The COVID-19 pandemic can affect the elderly population’s general health. This study aimed to compare the effects of a remote home-based exercise program to improve the mental state, balance, and physical function and to prevent falls in adults aged 65 years and older during the COVID-19 pandemic in Seoul, Korea. Material/Methods Seventy participants were randomly assigned to an experimental group of 35 participants who underwent a remote home-based fall prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 66 publications
3
36
0
11
Order By: Relevance
“…In a randomized controlled trial with older adults that evaluated the effects of strength training performed at home without online supervision, it was possible to observe a significant improvement in lower limb strength in the experimental group compared with the control [ 19 ]. A study carried out between June and July 2021 evaluated the effects of a remote home-based exercise program on mental state, balance, and physical function and prevention of falls in the older adult [ 20 ]. The fall prevention exercise program improved all study variables, but pre-study exercise was not indicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized controlled trial with older adults that evaluated the effects of strength training performed at home without online supervision, it was possible to observe a significant improvement in lower limb strength in the experimental group compared with the control [ 19 ]. A study carried out between June and July 2021 evaluated the effects of a remote home-based exercise program on mental state, balance, and physical function and prevention of falls in the older adult [ 20 ]. The fall prevention exercise program improved all study variables, but pre-study exercise was not indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Engaging predominantly in domestic activities can decrease physical activity levels, resulting in a decline in functional capacity and, consequently, in an increase in the risk of falls [ 29 ]. Some studies showed association between physical activity levels and reduced depressive symptomatology in older adults who were physically active during social distancing via in-person training, showing that the ones who managed to maintain or improve their physical activity level did not exhibit new depressive symptoms [ 20 , 26 , 27 , 28 , 29 ]. These findings are similar to our results and provide evidence of the protective effect of physical activity on depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the control group, the experimental group showed significant changes in all the dependent variables except dynamic balance ( p < 0.05). 40 Another study found that a community-delivered group-based functional power training program running for 12 weeks and comprising two 60 min sessions per week for frail older adults at local senior activity centers resulted in significantly better improvement in the SPPB test in the intervention arm than in the control arm. 21 In our study, the intervention arm showed improvements in the grip strength, sit-to-stand, four-meter gait speed, SPPB, single-leg standing, and timed up and go tests relative to baseline, similar to the results of both of these 2021 studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, access to exercise equipment within the home tends to be very limited. Therefore, studies determining the impact of lockdown measures associated with the pandemic on fitness levels and exploring how remote home-based exercise programs might minimize losses in functional capacity and perceived loneliness in older adults become imperative 13 .…”
Section: Introductionmentioning
confidence: 99%